Analysis of Smart City Quick Win Program Implementation Using Fuzzy BWM and TOPSIS in Manado and Tomohon - Puteri Justia Kardia Momuat Wahani; Sri Yulianto Joko Prasetyo; Indrastanti R. Widiasari; Johan J. C. Tambotoh (ISB Atma Luhur, 2026)
This study analyzes the implementation quality of smart city quick win programs in Manado and Tomohon using the Fuzzy Best-Worst Method (BWM) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The evaluation covers 12 quick win programs across six smart city dimensions: smart governance, smart branding, smart economy, smart living, smart society, and smart environment. The assessment uses 12 criteria derived from government smart city evaluation elements, including policy alignment, problem and goal clarity, public benefit, implementation readiness, technological readiness, governance ownership, service performance, monitoring and evaluation, and sustainability. Data were collected from official documents, evidence catalogs, interviews, expert assessments from 20 respondents, and government evaluation records. The novelty of this study lies in the development of a program-level evaluation model that integrates Fuzzy BWM for criteria weighting and TOPSIS for ranking quick win programs. Unlike previous studies that mainly evaluate smart city performance at the city or dimension level, this study positions quick win programs as concrete implementation units. The results show that problem and goal clarity, direct public benefit, and service performance are the most influential aspects in determining implementation quality. The TOPSIS results identify Manado 360 and SmartGov/PONTER as the strongest programs, while the city-level comparison shows that Manado has more consistent implementation quality than Tomohon. This study contributes a structured decision-support model for evaluating and improving smart city quick win programs.